TO THE MATTER OF TAKING INTO ACCOUNT OF PECULIARITIES OF INSTRUMENTAL STEELS AT PRODUCTION OF MATRIX OF COLD-UPSETTING AUXILIARIES - V. M. Kenjko; I. N. Stepankin (Литьë и металлургия)
The comparative analysis of operation characteristics of cold heading female moulds, produced from steels P6M5 and X12M, in relation with their structure and stressed state, is carried out.